Pelatihan Pendekatan Teaching at the Right Level (TaRL) dan Culturally Responsive Teaching (CRT) pada Guru Sekolah Dasar Pelatihan Pendekatan Teaching at the Right Level (TaRL) dan Culturally Responsive Teaching (CRT) pada Guru Sekolah Dasar - Prafitasari, Ferrinda; Purbosari, Para Mitta; Susilowati, Dewi; Pujiyana; Rosyid, Ahmad; Pratama, Sekar Ayu Pramudya; Maharani, Sahda Hasannah Zain (Universitas Veteran Bangun Nusantara, 2025)
Teachers at SD Negeri Pundungrejo 03 have difficulty implementing differentiated learning and tend to use existing learning devices without modification. This community service activity aims to improve teachers' ability to implement the differentiated Independent Curriculum with the Teaching at the Right Level (TaRL) and Culturally Responsive Teaching (CRT) approaches. This activity was carried out directly at SD Negeri Pundungrejo 03 Sukoharjo. The community service implementation procedure refers to the APTE stages (Needs Analysis, Training and Mentoring, Action, and Evaluation). The pretest results showed that teachers' initial understanding of the development of TaRL and CRT-based learning devices was still low. However, after mentoring, the posttest results showed a significant increase in teacher knowledge and skills. Indicators of success can be seen from the ability of teachers to develop learning devices according to students' thinking levels and their cultural backgrounds. Teachers also showed high enthusiasm in improving the quality of the learning process.